On the ease of overstating the fiscal stimulus in the US, 2008-9 - Joshua Aizenman; Gurnain Kaur Pasricha (University of California, Economics Department, 2010)
This note shows that the aggregate fiscal expenditure stimulus in the United States, properly adjusted for the declining fiscal expenditure of the fifty states, was close to zero in 2009. While the Federal government stimulus prevented a net decline in aggregate fiscal expenditure, it did not stimulate the aggregate expenditure above its predicted mean. We discuss the implications of limitations on states' ability to run deficits for the design of fiscal stimulus at the federal level. We devote particular attention to intertemporal moral hazard concerns in a federal fiscal system, and ways to address these concerns.
Keywords: E62; F36; H77; 330; fiscal union; federal fiscal expenditure; fiscal policy; moral hazard